The currency of the People's Republic of China and production fragmentation - Nobuaki Yamashita (Asian Development Bank Institute (ADBI), 2011)
This paper examines how an appreciation of the currency of the People's Republic of China (PRC) - renminbi - affects the country's exports in the context of production fragmentation, using a panel data set of the PRC's trade for 1992/93-2008/09. It constructs two exchange rates for renminbi: one is a bilateral real exchange rate and the other is a real effective exchange rate against East Asian component suppliers. It is found that appreciation of the renminbi would somewhat offset a reduction in the volume of the PRC's exports induced by lower importing costs of components. Hence, evidence casts further doubts on the efficacy of further unilateral reform of the renminbi exchange rate regime on correcting trade imbalances.
Keywords: F14; F23; F31; 330; Renminbi; Aufwertung; Außenhandelseffekt; Außenhandelsstruktur; China